Potentials of transcutaneous ultrasound investigation of neck and mediastinum at cancer of the upper third of esophagus - V. I. Kazakevich; L. A. Mitina; S. O. Stepanov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Aim of investigation. To analyze potentials of transcutaneous US in assessment of local progression of cancer of cervical and upper thoracic regions of the esophagus.Material and methods. Investigation with application of transcutaneous US of neck and mediastinum was carried out in 432 patients with esophageal cancer. Involvement of cervical and upper thoracic parts was present in 38 patients, 22 of them were operated. Results. US allowed to visualize involvement of cervical and upper thoracic regions of the esophagus in all patients, to detect extent of the lesion, to diagnose correctly depth of invasion, neighboring organs and structures involvement.Conclusions. Transcutaneous US is effective method of visualization of cancer of cervical and upper thoracic regions of the esophagus, assessment of depth of tumor invasion and involvement of neighboring organs and structures in this group of patients.